Efeito da administração aguda de creatina sobre a memória em ratos - Myskiw, Jociane de Carvalho (2005)
Glucose is the most important energy substrate for the central nervous system. Besides its energetic function, glucose facilitates memory in experimental animals, an effect that has been related to its energy functions. Other important cerebral energy substrate is creatine, which is endogenously synthesized and converted to phosphocreatine, an immediate and important source of high-energy phosphates, in a reaction catalysed by the enzyme creatine kinase. Athletes use this supplement to improve high intensity exercise performance. In addition creatine protects against convulsions induced by methylmalonic acid and N-methyl-D-aspartate. The aims of the present work, were to verify the possible effects of the acute administration of creatine on the acquisition, consolidation and evocation of the memory of the inhibitory avoidance task in rats; to verify whether creatine alters anxiety, locomotor activity and footshock sensitivity in rats; to determine whether creatine causes state dependence in the inhibitory avoidance task and whether glutamate-mediated mechanisms are involved in the deleterious effects of creatine on inhibitory avoidance memory. The results obtained in the current work show that creatine, administered 15 minutes before training (3.75 mg/kg, i.p.), immediately after training (1.87 mg/kg, i.p.) and 15 minutes before testing (7.5 mg/kg, i.p.), impaired animal performance at testing, and that these effects were not due to alterations in anxiety, locomotor activity or footshock sensitivity. Creatine (1.87 mg/kg, i.p.) administration, immediately after training, caused state dependence in the inhibitory avoidance task. Since creatine protects against the glutamate-mediated neurotoxicity, we decided to investigate whether glutamate receptors are involved in the deleterious effects of creatine on memory. The intra-hippocampal administration of glutamate, at a dose that had no effect on memory, prevented the amnestic effect of systemically administered creatine. Accordingly, creatine at a dose that had no effect on memory per se, reverted the facilitatory effects of glutamate on the memory of the inhibitory avoidance task. Moreover, MK-801 and creatine caused cross-state dependence in the inhibitory avoidance task, providing additional pharmacological basis for a putative action of creatine on the glutamatergic system, particularly the NMDA receptor. Considering the results obtained in the present work we conclude that creatine impairs the acquisition, consolidation and evocation of inhibitory avoidance task. The effects of creatine on memory seems to be due state dependence associated with NMDA receptor blockade.